If z1=3+2i and Z2=1-i,

Asked by Preemnath Katare | 11th Jun, 2010, 02:08: PM

Expert Answer:

Dear Student,
i) Z1 Z2 = (3+2i)(1-i) = 3 - 3i + 2i + 2 = 5 - i
ii) Z1/Z2 = (3+2i)/(1-i) = (3+2i)(1+i)/(1-i)(1+i) = (3 + 3i + 2i - 2)/(1 + 1) = (1 + 5i)/2 = (0.5 + 2.5i)
iii) Z1 + Z2 = 3 + 2i + 1 - i = 4 - i
iv) Z1 - Z2 = 3 + 2i - 1 + i = 2 + 3i
Regards,
Topperlearning

Answered by  | 14th Jul, 2010, 03:11: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.